Peran Guru dan Siswa dalam Mengoptimalkan Pendidikan Lingkungan Hidup di Sekolah - Rahayu, Rindi; Rahmawati, Ani; Jeni, Siti Susi; Rachman, Meylia Alidya; Alpian, Yayan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Environmental education is very important to be learned by the people of Indonesia. From a young age to adulthood, we are always given understanding and literacy by both of our parents. That's why Environmental Education is very important for the people of Indonesia. Understanding and literacy have been learned since we were young until adulthood, one of which is throwing trash in its place. This knowledge can become a habit and will always last long in our minds and hearts. We will always remember that throwing trash in its place is something that must be accustomed for the people of Indonesia. This research will outline the role of a teacher and students in an effort to optimize Environmental Education in elementary schools. All teachers and staff, including the principal of SDN Kutawargi 1, have been using several strategies to optimize facilities and infrastructure at SDN Kutawargi 1. From the research, it is implied that with the lack of facilities and infrastructure in schools, preserving the environment is very important for all students in the school. There is no reason for students not to preserve the school environment or its surroundings. The aim of this research is to find out the extent of the role of a teacher and students in implementing environmental education at SDN Kutawargi 1.